Enhancement of the turbulent convective heat transfer in channels through the baffling technique and oil/multiwalled carbon nanotube nanofluids - Menni, Younes; Chamkha, Ali J.; Ghazvini, Mahyar; Ahmadi, Mohammad Hossein; Ameur, Houari; Issakhov, Alibek; İnç, Mustafa (Taylor & Francis Inc, 2020)
An attempt is made to improve the overall performances of channel heat exchangers. The techniques of baffles and nanofluids are combined to enhance the dynamic and thermal behaviors within the channel exchanger. Baffles under various attack angles are used as vortex generators. In addition, oil/multiwalled carbon nanotubes (MWCNT) is used as a working fluid. Both inclinations in the upstream and downstream directions were considered, referenced as Case A (UIB) and Case B (BIB), respectively. While the channel equipped with vertical baffles is referenced as Case C. The proposed models with combined techniques allowed a considerable enhancement in the overall efficiency. The comparison between the three cases revealed that the most significant value of thermal enhancement factor (TEF) of 5.634 was reached with vertical baffles (Case C) at the highest value of Reynolds number. When using inclined baffles, the 75 degrees upstream attack angle (Case A) allowed the highest TEF of 4.814, compared with Case B.
Keywords: Rectangular Channel; Thermal Performance; Hybrid Nanofluids; Pressure-Drop; Energy; Flow; Exchangers; Existence; Collector; Fin